English: English - BALCI, Senay; AKBAYIR, Serin; BOZLU, Murat; TAMER, Lulufer (Journal of Medical Biochemistry, 2022)
Background: Prostate cancer is a slowly progressing cancer seen in older men. Despite advances, prostate cancer remains a major medical problem for affected men. Risk factors of prostate cancer include age, race and prostate cancer family history. Prostate cancer may occur at different frequencies between ethnic populations and countries. Currently, studies on genetic risk factors in prostate cancer etiology have been increasing, and the results show that they are interrelated.Nitric oxide synthase is the enzyme that converts L-arginine to Nitric Oxide. It has been shown that changes in endothelial nitric oxide synthase have an important role in carcinogenesis and the cardiovascular system. There are studies evaluating the relationship of endothelial nitric oxide synthase gene T786C polymorphism with prostate cancer risk in different populations and the results are contradictory.Based on this, we aimed to reveal whether endothelial nitric oxide synthase T786C polymorphism exists in the participants and whether it was associated with prostate cancer.Methods: Archival samples included in this study were whole blood samples taken from patients who were grouped according to prostate biopsy pathology results and from healty participants. DNA was isolated from these whole blood samples, and real-time polymerase chain reaction analysis was performed for endothelial nitric oxide synthase T786C polymorphism with LightCycler 480 II. Measured free and total prostate specific antigen serum levels were evaluated retrospectively.Results: There was a statistically difference between patient-healthy control and control-healthy control groups in terms of genotype distributions for endothelial nitric oxide synthase T786C polymorphism. Healthy controls were more likely to have TC and CC genotypes, and C allele than the other two groups.Conclusions: Contrary to the previous studies, in this study, no risk relationship was found between endothelial nitric oxide synthase T786C polymorphism and prostate cancer in the Turkish population.
Keywords: English